Optimalisasi Omzet Penjualan Kaos Pada Usaha Konveksi Rumah Kaos Lombok Menggunakan Metode Simpleks - Ratih, Wahyu Erinna; Setiandini, Gifani Putri; Risnawati, Risnawati; Maharani, Andika Ellena Saufika Hakim; Alfian, Muhammad Rijal (JSN : Jurnal Sains Natural, 2025)
Rumah Kaos convection is a manufacturing company that focuses on producing high-quality t-shirts with a variety of design options. This research aims to optimize turnover from t-shirt production by applying a linear programming approach using the simplex method. The data analyzed includes product type, raw materials, working time and selling price. The analysis process is carried out by compiling objective functions, constraint functions, and simplex table modeling. The results of this research show the optimal combination in raw material allocation that can maximize profits. It is hoped that these findings will serve as a strategic guide for entrepreneurs in planning production efficiently and achieving sustainable business growth.